Determinants of Acute Kidney Injury and Renal Function Decline After Endovascular Abdominal Aortic Aneurysm Repair. (December 2017) - Statius van Eps, Randolph G.; Nemeth, Banne; Mairuhu, Ronne T.A.; Wever, Jan J.; Veger, Hugo T.C.; van Overhagen, Hans; van Dijk, Lukas C.; Knippenberg, Bob
Abstract : Objective/Background: Endovascular aneurysm repair (EVAR) may be associated with renal injury and more insight is needed into potential risk factors. The aim was to identify clinical, anatomical, and peri-procedural parameters as potential risk factors for the occurrence of acute kidney injury (AKI) and to evaluate chronic kidney disease (CKD) after EVAR. Methods: A cohort of 212 consecutive patients who underwent elective EVAR for abdominal aortic aneurysm from January 2009 to October 2016 was included. A subgroup of 149 patients with 2 years follow-up was compared with a set of 135 non-operated aneurysm patients with smaller aneurysms (similar cardiovascular risk profile) to assess CKD. Primary outcomes were AKI (Acute Kidney Injury Network criteria) and CKD measured by estimated glomerular filtration rate (Kidney Disease Improving Global Outcomes guidelines). For AKI, candidate risk factors were identified by univariate and multivariate logistic regression analysis; for chronic renal function decline, risk factors were identified using Cox regression analysis. Results: AKI occurred in 30 patients (15%). On multivariate analysis, the use of angiotensin II blocker (odds ratio [OR] 4.08, 95% confidence interval [CI] 1.38–12.07) and peri-operative complications (OR 3.12, 95% CI 1.20–8.10) were independent risk factors for AKI, whereas statin use was a protective factor (OR 0.19, 95% CI 0.07–0.52). EVAR resulted in a significant increase (23.5%) in the occurrence of CKD compared with the control group (6.7%; p <.001). On univariate and multivariate Cox regression the risk factors: aortic neck diameter (per mm increase) (hazard ratio [HR] 1.13, 95% CI 1.02–1.25), renal artery stenosis >50% (HR 2.24, 95% CI 1.05–4.79), and the occurrence of AKI (HR 2.19, 95% CI 0.99–4.85) were significant predictors of CKD. Conclusion: This study identified use of angiotensin II blockers and peri-operative complications as risk factors for AKI. In addition, the problem of renal function decline after EVAR is highlighted, which indicates that prolonged protective measures (e.g., in those patients at high risk) over time are needed to improve patient outcomes.